القرينة وعلاقتها بالمعنى والمراد، دراسة بلاغية أصولية: (al-Qarina and Its Relation with the Meaning: a Rhetotical and Usuli Study) - محمد بن يونس,; باطاهر, (At-Tajdid - Intellectual Refereed Journal, 2022)
-